SPA Philosophy as a Tourism Support - Case Study on Thai SPA and Bali SPA - Phattharachai Uthaphan; I Nengah Alit Nuriawan (Samā Jiva Jnānam (International Journal of Social Studies), 2024)
The SPA industry, a vital component of wellness tourism, offers unique experiences deeply rooted in cultural and natural contexts. This study explores thedistinctive philosophies of Thai and Balinese SPAs, examining their contributions totourism through a comparative analysis. Thai SPAs emphasize balance and energyflow, integrating traditional Thai massage techniques, herbal treatments, and Buddhistprinciples to create a holistic wellness experience. Conversely, Balinese SPAs focuson harmony with nature and spiritual serenity, reflecting the island's Hindu-Buddhistheritage. Treatments in Balinese SPAs often use local ingredients and are performedin serene natural settings, enhancing the connection between guests and the island’scultural and natural beauty. The methodology involved a comprehensive literaturereview and content analysis of academic articles, books, and industry reports, followedby a comparative analysis to highlight the unique features and commonalities betweenthe SPA philosophies of Thailand and Bali. The findings reveal that both SPAtraditions play a crucial role in enhancing cultural tourism by offering authenticexperiences that connect visitors with local traditions and practices. Additionally, theseSPAs contribute to sustainable tourism by utilizing local resources and supportingtraditional practices, which helps preserve cultural heritage and promotes economicgrowth in local communities. The study concludes that the distinctive philosophies ofThai and Balinese SPAs not only provide therapeutic benefits but also serve as culturalambassadors and promoters of sustainable tourism. As global interest in wellnesstourism continues to rise, these unique SPA experiences will remain pivotal inattracting tourists seeking comprehensive well-being experiences, thereby supportingthe overall sustainability and appeal of their respective destinations.